Is GFR decline induced by SGLT2 inhibitor of clinical importance? - Günes-Altan, Merve; Bosch, Agnes; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Cardiovascular Diabetology, 2024)
Background: Use of sodium-glucose-cotransporter-2 (SGLT2) inhibitors often causes an initial decline in glomerular filtration rate (GFR). This study addresses the question whether the initial decline of renal function with SGLT2 inhibitor treatment is related to vascular changes in the systemic circulation. Methods: We measured GFR (mGFR) and estimated GFR (eGFR) in 65 patients with type 2 diabetes (T2D) at baseline and after 12 weeks of treatment randomized either to a combination of empagliflozin and linagliptin (SGLT2 inhibitor based treatment group) (n = 34) or metformin and insulin (non-SGLT2 inhibitor based treatment group) (n = 31). mGFR was measured using the gold standard clearance technique by constant infusion of inulin. In addition to blood pressure (BP), we measured pulse wave velocity (PWV) under standardized conditions reflecting vascular compliance of large arteries, as PWV is considered to be one of the most reliable vascular parameter of cardiovascular (CV) prognosis. Results: Both mGFR and eGFR decreased significantly after initiating treatment, but no correlation was found between change in mGFR and change in eGFR in either treatment group (SGLT2 inhibitor based treatment group: r=-0.148, p = 0.404; non-SGLT2 inhibitor based treatment group: r = 0.138, p = 0.460). Noticeably, change in mGFR correlated with change in PWV (r = 0.476, p = 0.005) in the SGLT2 inhibitor based treatment group only and remained significant after adjustment for the change in systolic BP and the change in heart rate (r = 0.422, p = 0.018). No such correlation was observed between the change in eGFR and the change in PWV in either treatment group. Conclusions: Our main finding is that after initiating a SGLT2 inhibitor based therapy an exaggerated decline in mGFR was related with improved vascular compliance of large arteries reflecting the pharmacologic effects of SGLT2 inhibitor in the renal and systemic vascular bed. Second, in a single patient with T2D, eGFR may not be an appropriate parameter to assess the true change of renal function after receiving SGLT2 inhibitor based therapy. Trial registration: clinicaltrials.gov (NCT02752113).
CRIS-Team Scopus Importer:2024-06-14
Keywords: GFR decline; PWV; SGLT2 inhibitors